Evaluation of lung function on impulse oscillometry in preschool children born late preterm. Issue 4 (2nd February 2016) - Er, Ilkay; Gunlemez, Ayla; Uyan, Zeynep Seda; Aydogan, Metin; Oruc, Meral; Isik, Olcay; Arisoy, Ayse Engin; Turker, Gulcan; Baydemir, Canan; Gokalp, Ayse Sevim
Abstract: Background: There is a paucity of data on lung physiology in late‐preterm children, who may be exposed to a risk of decline in lung function during childhood. In this study, we evaluated lung function in preschool children born late preterm using impulse oscillometry (IOS), and compared the results with those obtained in healthy term‐born children. Methods: Children between 3 and 7 years of age who were born late preterm and who were being followed up at the outpatient clinic were included as the late‐preterm group. Age‐matched healthy term‐born children served as controls. A total of 90 late‐preterm and 75 healthy children were included in the study. At 5–20 Hz, resistance (R5–R20), reactance (X5–X20), impedans (Z5) and resonant frequency were measured on IOS. Results: Mean IOS R5 and R10 were significantly higher in the late‐preterm group than in the control group ( P  < 0.05). Mean R5, R10 and Z5 were statistically higher in late‐preterm children who had been hospitalized for pulmonary infection compared with the control group ( P  < 0.05). Mean R5, R10, R15, R20 and Z5 were significantly higher, and mean X10 and X15 significantly lower in late‐preterm children with passive smoking compared with late‐preterm children without passive smoking and controls ( P  < 0.05). Conclusion: Children born late preterm had signs of peripheral airway obstruction on IOS‐based comparison with healthy term‐born controls. Besides the inherent disadvantages of premature birth, hospitalization for pulmonary infection and passive smoking also seemed to adversely affect lung function in children born late preterm.